Penyuluhan Tentang Pola Hidup Sehat Lawan Covid-19 dengan Umbi Lokal sebagai Peningkat Daya Tahan Tubuh - Ferika Indrasari; Sri Suwarni; Eleonora Maryeta Toyo (Jurnal Pengabdian Masyarakat (abdira), 2022)
A healthy diet affects a person's level of fitness or endurance in fighting diseases, especially COVID 19. Local tubers are one of the traditional foods that can increase endurance. The purpose of the community of Sendang Mulyo Village, Semarang City is to use local tubers to increase body resistance.  The method of carrying out activities is carried out by counseling, discussing and evaluating knowledge with structured questionnaires which are carried out in the Sendang Mulyo Village office hall which is located at Jalan Ketileng Raya in Sendang Mulyo, Semarang City on August 26, 2020 starting at 09.00 to 12.00 WIB with 35 participants. members of the PKK, Sendang Mulyo Village. The result of the activity is the implementation of the activity well and smoothly. Based on the questionnaire data, there was an increase in the knowledge of the counseling participant respondents after being given counseling about the benefits of tubers on the immune system during the Covid-19 pandemic